(Re)configuração identitária de uma professora de língua inglesa por meio da pesquisa colaborativa - Ticks, Luciane Kirchhof (Linguagens & Cidadania, 2017)
This article discusses some of the results obtained in the development of a collaborative research which focused on the (re)configuration of pedagogical practices and identities of an English teacher. The data were collected through reflective sessions and diaries and the procedures of analysis were basically of Critical Discourse Analysis. The results indicate the collaborative research allowed the participant to reconfigure her pedagogical practice and her identity as an English teacher. This research also highlights the need for the development of continuing education programs in State schools so that representations of teaching and learning, as well as the constitution of professional identities, can be problematized in the process of building a reflective education culture.